2011
DOI: 10.1128/aem.00764-11
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Community Successional Patterns during Forest Ecosystem Restoration

Abstract: Soil microbial community characterization is increasingly being used to determine the responses of soils to stress and disturbances and to assess ecosystem sustainability. However, there is little experimental evidence to indicate that predictable patterns in microbial community structure or composition occur during secondary succession or ecosystem restoration. This study utilized a chronosequence of developing jarrah (Eucalyptus marginata) forest ecosystems, rehabilitated after bauxite mining (up to 18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
155
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(175 citation statements)
references
References 61 publications
18
155
2
Order By: Relevance
“…In a dry environment, microbial succession may lag behind plant succession, but plant and microbes demonstrate a similar succession pattern (Lozano et al, 2014). Previous studies reported that bacteria and fungi evolved along different trajectories under various conditions, such as secondary succession in a restored ecosystem (Banning et al, 2011;Li et al, 2013a), shrub encroachment (Yannarell et al, 2014), and the primary succession of lava flows (Cutler et al, 2014) and glacier soils (Brown and Jumpponen, 2014). The different succession patterns were determined by the range of microbial physiologies, dispersal ability, and assembly pattern .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a dry environment, microbial succession may lag behind plant succession, but plant and microbes demonstrate a similar succession pattern (Lozano et al, 2014). Previous studies reported that bacteria and fungi evolved along different trajectories under various conditions, such as secondary succession in a restored ecosystem (Banning et al, 2011;Li et al, 2013a), shrub encroachment (Yannarell et al, 2014), and the primary succession of lava flows (Cutler et al, 2014) and glacier soils (Brown and Jumpponen, 2014). The different succession patterns were determined by the range of microbial physiologies, dispersal ability, and assembly pattern .…”
Section: Discussionmentioning
confidence: 99%
“…Banning et al (2011) showed that the bacterial community successional trend became more similar to those of the surrounding non-mined forest with increased rehabilitation age, but fungi did not show a similar successional trajectory. Yannarell et al (2014) found that both bacterial and fungal communities demonstrated significant variation along transects spanning the prairie-shrub-forest continuum, but their predominant patterns were different.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, the quantity, quality, community structure, and activity of soil microorganisms and soil fauna, which occur mainly in the upper part of the soil profile, also depend on soil physical and chemical properties (Moorhead et al 2003;Carson et al 2007;Rousk et al 2010;Banning et al 2011;Świtoniak et al 2014). Surface soil horizons are also characterized by the highest content of soil organic carbon and nitrogen and the concentration of organic carbon and nitrogen in soils is highly related to other soil physical and chemical parameters such as texture (mainly clay fraction content), mineral composition (mainly quantity and quality of clay minerals), moisture, pH, and the content of common and less common chemical elements (Schimel et al 1994;Balesdent et al 2000;Sjögersten et al 2006;Xu et al 2016;Szymański et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soil microbial communities may provide early indication of soil changes (Harris, 2009;Banning et al, 2011), and are increasingly used to assess ecosystem responses * Corresponding author. E-mail: zhenghua@rcees.ac.cn to environmental perturbations (Harris, 2003;van Dijk et al, 2009;Lewis et al, 2010;Banning et al, 2011) because of its rapid response to anthropogenic disturbances relative to soil biogeochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…E-mail: zhenghua@rcees.ac.cn to environmental perturbations (Harris, 2003;van Dijk et al, 2009;Lewis et al, 2010;Banning et al, 2011) because of its rapid response to anthropogenic disturbances relative to soil biogeochemical properties. These responses have been assessed using soil biological indicators such as the phospholipid fatty acid (PLFA) profiles to reflect the structure of the soil microbial community (Iovieno et al, 2010), and soil enzyme activities to reflect their functional capacity (Rivas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%